Does the choice of the measuring technique affect the comparison of fit between zirconia and cobalt-chromium prostheses? - Elie E. Daou; Pascale Salameh (Wolters Kluwer Medknow Publications, 2024)
Aims: The objectives of the study were to compare the adaptation of presintered zirconia and cobalt- chromium prostheses using microcomputed tomography (μCT), scanning electron microscopy (SEM), and stereomicroscope (SM). Materials and Methods: Twenty-four fixed dental prostheses (FDPs) were fabricated on metal abutments, duplicated from maxillary first premolar and first molar prepared on a typodont model. Teeth were reduced to obtain chamfer of 1.2 mm and reduction occlusaly of 2 mm occlusal. Scanning of the abutments was done with random assignment to two groups receiving the FDPs made from soft-milled Co-Cr (n = 12) and zirconia (n = 12). Marginal and internal gaps were assessed using three evaluation techniques (X-ray microcomputer tomography, SEM, and stereomicroscopy). Statistical Analysis Used: Comparison of the results was made using Levene and analysis of variance tests (α =0.05). Results: Irrespective of the material tested, statistical differences were found between the measuring techniques (P = 0.001 overall); the obtained mean gaps were for CT scan (92.60 ± 13.31), for SEM (101.92 ± 23.03), and for SM (113.44 ± 14.68): the multiple comparisons between techniques found a significant difference between CT and SM (P < 0.001), and SEM and SM (P = 0.025). When materials were compared within each measuring technique, Co-Cr showed lower values compared to zirconia in SEM (P < 0.001) and Stereo (P = 0.049); similar results were found in CT. Conclusions: Results values differed with the chosen measuring technique. Co-Cr prostheses had a better fit than zirconia prostheses in SEM and Stereo. μCT showed comparable results to SEM, smaller than SM results.